Median Lethal Salinity (MLS- 50 96H) of certain freshwater aquaculture fish species (Order: Cypriniformes) from coastal mainland of Sundarban, India - Das, Utpal Kumar; Dubey, Sourabh Kumar; Trivedi, R K; Chand, B K; Beg, M M (Journal of the Inland Fisheries Society of India, 2020)
The present study evaluated salinity tolerance of nine commonly cultivated freshwater cyprinids (order: Cypriniformes) from coastal mainland of Sundarban, India, where salinity intrusion is a recurrent phenomenon. After 100% mortality of all the fishes had been obtained from 15 to 20 g l-1 salinity levels in the first phase of range-finding test, the median lethal salinity (MLS-50 96h) was determined for every fishes by direct exposure to various salinities (5-18 g l-1) in laboratory. Among the cyprinid group, the silver barb Barbonymus gonionotus showed greater tolerance to salinity (14.23 g l-1) followed by Cyprinus carpio (13.03 g l-1) and Systomus sarana (12.72 g l-1). Among the Indian major carps, Labeo rohita represented highest salinity tolerance (11.09 g l-1). Among all experimented fishes, Labeo bata exhibited least tolerant to increasing salinity (8.14 g l-1) followed by Catla catla and Hypophthalmichthys molitrix (9.04 and 9.38 g l-1 respectively). The results of the present experiment indicated that salinity plays a significant role in the survival of freshwater stenohaline species and sub-lethal salinities of the most of the species are up to and below 10 g l-1 salinity. Under the changing climate scenario, some freshwater aquaculture species such as Barbonymus gonionotus, Cyprinus carpio, Systomus sarana, Labeo rohita can be encouraged in the Indian Sundarban and other tropical deltas where brackish water intrusion is a frequent phenomenon. Key words Median lethal salinity (MLS-50 96h); Cyprinids; Stenohaline fish; Sundarban; Salinity intrusion